Human T cell lymphotropic virus type 1 infection among men who have sex with men in Central Brazil - Castro,Lisie Souza (2018)
ABSTRACT Human T cell lymphotropic virus type 1 (HTLV-1) was the first retrovirus discovered in humans and is endemic in several parts of the world. Because of risk behaviors, mainly sexual, men who have sex with men (MSM) are at high risk of acquiring HTLV-1 infection. A cross-sectional study was performed to estimate the prevalence of HTLV-1 infection, to characterize genetically HTLV-1 sequences and to identify risk behaviors associated with this infection among MSM in Central Brazil. A total of 430 MSM were enrolled in this study and three were shown to be HTLV-1 infected, prevalence of 0.7% (95% confidence interval: 0.4-0.9). Phylogenetic analysis showed that all HTLV-1 positive samples belonged to Cosmopolitan subtype Transcontinental subgroup A. Although the prevalence rate of HTLV-1 infection found in this study was similar to that observed among Brazilian blood donors, additional HTLV-1 preventive interventions need to be further implemented because this population is engaged in high-risk sexual behavior.